Investing in Public Infrastructure : Roads or Schools? - Atolia, Manoj; Li, Bin Grace; Marto, Ricardo; Melina, Giovanni (Washington, D.C. : International Monetary Fund, 2017)
Why do governments in developing economies invest in roads and not enough in schools? In the presence of distortionary taxation and debt aversion, the different pace at which roads and schools contribute to economic growth turns out to be central to this decision. Specifically, while costs are front-loaded for both types of investment, the growth benefits of schools accrue with a delay. To put things in perspective, with a 'big push,' even assuming a large (15 percent) return differential in favor of schools, the government would still limit the fraction of the investment scale-up going to schools to about a half. Besides debt aversion, political myopia also turns out to be a crucial determinant of public investment composition. A 'big push,' by accelerating growth outcomes, mitigates myopia-but at the expense of greater risks to fiscal and debt sustainability. Tied concessional financing and grants can potentially mitigate the adverse effects of both debt aversion and political myopia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet